Impact of Non‐Stoichiometric Phases and Grain Boundaries on the Nanoscale Forming and Switching of HfOx Thin Films - Niclas Schmidt; Nico Kaiser; Tobias Vogel; Eszter Piros; Silvia Karthäuser; Rainer Waser; Lambert Alff; Regina Dittmann (Advanced Electronic Materials, 2024)
Abstract HfO2 is one of the most common memristive materials and it is widely accepted that oxygen vacancies are prerequisite to reduce the forming voltage of the respective memristive devices. Here, a series of six oxygen engineered substoichiometric HfO2 − x thin films with varying oxygen deficiency is investigated by conductive atomic force microscopy (c‐AFM) and the switching process of substoichiometric films is observed on the nanoscale. X‐ray diffractometry (XRD) exhibits a phase transition from stoichiometric, monoclinic HfO2 toward oxygen deficient, rhombohedral HfO1.7. The conductance of HfO2 − x is increasing with increasing oxygen deficiency, which is consistent with the increasing prevalence of the highly conductive rhombohedral phase. Simultaneously, c‐AFM reveals significant local conductivity differences between grains and grain boundaries, regardless of the level of oxygen deficiency. Single grains of highly oxygen deficient samples are formed at significant lower voltages. The mean forming voltage is reduced from (7.0 ± 0.6) V for HfO2 to (1.9 ± 0.8) V for HfO1.7. Resistive switching on the nanoscale is established for single grains for the highest deficient thin film samples. The final resistance state is thereby dependent on the initial conductivity of the grains. These studies offer valuable insights into the switching behavior of memristive polycrystalline HfO2.